A different kind of partnership: an infrastructure performance stock exchange. Issue 1 (25th April 2020) - Posavljak, Milos; Tighe, Susan L; Larson, Nick; Rapp, Cameron
Abstract : Typically, public–private partnerships are constrained to be 'mega' construction projects and long-term arrangements. This paper introduces a practical mechanism for a novel public–private partnership modelled on the concepts of market trading (i.e. stock exchange). The ultimate mega project is the management of an entire infrastructure asset network by a government agency (federal, provincial, local, etc.). Hundreds of billions of dollars are spent each year in North America on the upkeep of public infrastructure (roads, underground, buildings, parks, etc.). Yet, according to current projections, this is still far short of the funding that is required to achieve acceptable levels of performance or service. A transparent, evidence-based and auditable process for deriving a universal infrastructure asset performance stock measure is introduced. Rather than being based on asset age, as the current 'old infrastructure order' is, the 'new infrastructure order' of asset management is based on the principles of reliability (risk) engineering as applied to corporate information.